2015
DOI: 10.1016/j.jssc.2015.07.032
|View full text |Cite
|
Sign up to set email alerts
|

Thermochemistry of perovskites in the lanthanum–strontium–manganese–iron oxide system

Abstract: of Perovskites in the lanthanumstrontium-manganese-iron oxide system, Journal of Solid State Chemistry, http://dx.Abstract The enthalpies of formation from binary oxides of perovskites (ABO 3 ) based on lanthanum strontium manganite La(Sr)MnO 3 (LSM) and lanthanum strontium ferrite La(Sr)FeO 3 (LSF) and mixed lanthanum strontium manganite ferrite La(Sr)Mn(Fe)O 3 (LSMF) were measured by high temperature oxide melt solution calorimetry. Using iodometric titration, the oxygen content was derived. The perovskites … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
6
0

Year Published

2017
2017
2025
2025

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 41 publications
(45 reference statements)
0
6
0
Order By: Relevance
“…Research has shown that the magnetic and transport properties of La 1-x Sr x Mn 1-y Fe y O 3 perovskites are influenced by the Fe content. [18] Similarly, oxygen carriers based on Fe have displayed strong activity for H 2 O splitting as well as for total oxidation of CH 4 . [19] La 1-x Sr x FeO 3 have illustrated strong stability and repeatability for the oxidation of CH 4 .…”
Section: Introductionmentioning
confidence: 99%
“…Research has shown that the magnetic and transport properties of La 1-x Sr x Mn 1-y Fe y O 3 perovskites are influenced by the Fe content. [18] Similarly, oxygen carriers based on Fe have displayed strong activity for H 2 O splitting as well as for total oxidation of CH 4 . [19] La 1-x Sr x FeO 3 have illustrated strong stability and repeatability for the oxidation of CH 4 .…”
Section: Introductionmentioning
confidence: 99%
“…A 2 CO 3 generates carbon dioxide (CO 2 ) when it reacts with MoO 3 , and A 2 O–MoO 3 are produced. A 2 O–MoO 3 is a well-known oxide solvent, which is widely used for the high temperature calorimetry of complex oxides. The suppression of evaporation of MoO 3 flux by A 2 CO 3 and the growth of large crystals are empirically known, but its mechanism is not elucidated. The effect of inhibitor addition on evaporation rate of flux and growth rate of ruby crystal films should be further investigated.…”
Section: Introductionmentioning
confidence: 99%
“…are still intensively studied. Works focusing on various physical properties of the compounds, such as magnetoresistance (MR), crystal structure change, metal-insulator transition, specific heat, large magneto-caloric effect, and high electrical conductivity have been reported [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15][16]. These rare … (T MI ) of about 243 K. In case of T>T MI , the resisitivity as a function of temperature could be described by two different models, namely the variable range hopping (VRH) model or Arhenius model and the adiabatic small polaron hopping (ASPH) model but more in line with the second model (ASPH).…”
Section: Introduction mentioning
confidence: 99%
“…At the temperature less than 184 K, the resisitivity follows the Arhenius model (ln R varies as 1/T 0.25 ) while at higher temperatures it fits the metal-semiconductor model (ln R varies as 1/T). The electronic specific heat parameter γ varies with magnetic field at x = 0.06, but not at x = 0.15. earths manganite compounds have found a wide range of application, such as a mild hyperthermia mediator [1], magnetic refrigeration technology near room temperature [5], and a fuel cell cathode [7][8][9].Until now, the results of measurements and analysis of this material still make a lot of differences. Suppose La 1-x Sr x MnO 3 will change from orthorhombic (x<0.2) to rhombohedral (x>0.2) [1], at low temperatures, La 1-x Ca x MnO 3 structure will change from cubic to rhombohedral then to orthorhombic [2], while La 0.65 Ca 0.35-x Ba x MnO 3 has a rhombohedral crystal structure for x<0.15 and a cubic for 0.15<x<0.25 [3].…”
mentioning
confidence: 99%
See 1 more Smart Citation